Effective Public Relations Management in Building a Positive Image: A Case Study of Madrasah Ibtidaiyah Negeri 3 Cirebon - Norman, Efrita; Sulaiman, Sulaiman; Marliani, Lina; Widiantari, Dian; Rasini, Intan Nur; Dewi, Maftuhah (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study investigates the role of public relations management in building a positive image of educational institutions, focusing on Madrasah Ibtidaiyah Negeri 3 Cirebon. It aims to fill gaps in the literature regarding the empirical evidence of effective public relations strategies in madrasahs, providing both theoretical and practical contributions to the field of education. Design/methods/approach – The research employs a qualitative descriptive approach to deeply understand the public relations strategies at Madrasah Ibtidaiyah Negeri 3 Cirebon. Nine participants, including the head of the madrasah, public relations staff, teachers, and parents, were purposively selected. Data were collected through observations, in-depth interviews, and document analysis. Systematic data analysis involved narrative presentation, data reduction, and conclusion drawing/verification to identify patterns and causal relationships. Findings – The study found that integrated planning involving all stakeholders, active involvement of public relations staff, and adequate resource allocation were key to building a positive institutional image. Activities such as religious services, social services, and regular community engagement strengthened internal and external relations. Regular evaluations through scheduled meetings and feedback from the community helped identify shortcomings and improve public relations strategies. Research implications – The findings highlight the importance of collaborative and systematic public relations management in educational institutions. The study suggests that other educational institutions adopt similar approaches to enhance their public image, thereby increasing community trust and support.